2022
DOI: 10.1177/08980101221102691
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Meditation Profiles and Predictors in Nursing Students

Abstract: Background: Nursing students face unique academic and clinical workloads linked to increased stress. Previous studies indicate formal and informal mindfulness meditation provide stress-reducing benefits. This practice aligns with holistic nursing core values of self-care and self-reflection; little is known about meditation practice in nursing students. Objectives: Our study aimed to describe meditation practice and predictors in pre-licensure nursing students. Design: Cross-sectional, multi-site. Methods: Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…The findings revealed a positive association between self-compassion and patient care practices, aligning with previous literature indicating that self-compassion training enhances nurses' resilience, reduces burnout, and enables them to provide more compassionate care (17,18). Engaging in self-compassion practices is crucial for improving nurses' well-being and their professional quality of life, ultimately benefiting patient care (19). Group differences based on marital status indicated that unmarried nurses scored higher on self-compassion and patient care practices than married nurses.…”
Section: Discussionsupporting
confidence: 84%
“…The findings revealed a positive association between self-compassion and patient care practices, aligning with previous literature indicating that self-compassion training enhances nurses' resilience, reduces burnout, and enables them to provide more compassionate care (17,18). Engaging in self-compassion practices is crucial for improving nurses' well-being and their professional quality of life, ultimately benefiting patient care (19). Group differences based on marital status indicated that unmarried nurses scored higher on self-compassion and patient care practices than married nurses.…”
Section: Discussionsupporting
confidence: 84%
“…Johnson et al [7] investigated 417 nursing students from the viewpoint of mediation activities, such as mindful meditation, guided imagery, relaxation techniques, yoga with a focus on breathing, breathing exercises, prayer, and other spiritual activities. Johnson et al [7] found that 271 (65%) students reported meditation where the mediating students showed more self-compassion, happiness, and satisfaction with life and perceived less stress in comparison to students who did not meditate. Therefore, mediating habits may increase self-compassion.…”
Section: Introductionmentioning
confidence: 99%